An Investigation into the Precipitation of Nickel(II) and Cobalt(II) as Sulphides - Ashton M. Swartbooi; Robert van Hille; Alison E. Lewis (International Mineral Processing Congress, 2003)
"Nickel production by precipitation using hydrogen reduction generates an ammonium sulphate solution containing approximately 2g/L of nickel, and 1g/L of cobalt as an impurity of the process. Sulphide precipitation is an effective method for heavy metal removal, especially when compared to hydroxide processes: metals can be removed from solution at relatively low pH levels, small quantities of sludge are formed, and due to the high reactivity of sulphides the reactor retention time is reduced. However, the low solubility of sulphide species can lead to spontaneous nucleation of fines (due to higher supersaturation levels which are difficult to separate from solution, leading to reduced process efficiency. Using a fluidised bed reactor, fines formation can be minimised as the pellets provide a large surface area and promote heterogeneous nucleation.A synthetic nickel-cobalt ammonium sulphate solution was reacted with two forms of sulphide reagent: (a) a liquid sulphide solution and (b) gaseous hydrogen sulphide. A range of factors (including pH, reagent concentrations, metal to sulphide molar ratio, flow rates and recirculation rates) influencing the efficiency of the precipitation reaction have been studied. The efficiency of the precipitation reaction was measured using both metal recovery and fines formation as indicators.Figure 1 shows the effect of decreasing the metal:sulphide ratio (at constant SS = 2.725e+17), on the metal removal for liquid sulphide. By decreasing the metal:sulphide ratio, up to 99% removal of both nickel and cobalt could be achieved.These results also indicate that the precipitates that formed were polysulphides, since no sulphide was present in solution after the experiment. This would also indicate that a lower metal:sulphide ratio would be more favourable. However, decreasing this ratio (at constant metal concentrations) would lead to an increase in the fines concentration, because of increased supersaturation levels induced by the higher sulphide concentrations. To decrease the supersaturation, dilute solutions of either reagent would be employed."